A Semi-Stochastic Propagation Model for the Study of Beam Tilting in Cellular Systems - Konstantinos B. Baltzis (International Journal of Antennas and Propagation)
Base station antenna downtilt mitigates interference and improves the downlink performance of wireless systems. A semi-stochastic propagation model is presented and applied to the study of the impact of the base station beam tilting in cellular communications. The two-ray approximation of the proposed model is described analytically. Beam tilting is evaluated in relation to the base station antenna radiation pattern, the antennas height, the propagation environment, the bit error rate, and the signal-to-noise ratio at the receiver front end. Analytically derived expressions for the fading envelopes, the error probability, the optimum tilting angle, and the downlink capacity of a WCDMA system are derived. Theoretical analysis and simulation results are provided to show the characteristics of the model. Comparisons with data in the literature confirm its validity. Furthermore, the effect of beam tilting on system downlink performance in terms of bit error rate and capacity is investigated.